Urban sustainable development: inner logic and exploration in Guangzhou - Luo, Xiuming; Yan, Zedong; Ma, Chong; Xie, Jinlong (Frontiers in Built Environment, 2024)
Guangzhou, China, is experiencing numerous urban renewal activities. To achieve sustainable urban development, various related policies and strategies have been implemented. For better understanding of sustainable urban development, many research studies on urban sustainability assessment have been carried out. While traditional indicator indices are usually used to assess urban sustainability performance, few studies have been conducted on urban renewal activities. Moreover, urban development is a complex system and existing methods can no longer reflect the linkages between variables. Therefore, this study aims to develop a system dynamics model to simulate urban sustainability performance from the perspective of urban renewal. The system dynamics model consists of four subsystems, which are urban economic sector, social service sector, demolition and resettlement sector, and industrial development sector. The system dynamics model then uses seven scenarios to simulate the sustainability performance of Guangzhou city. The results show that the system dynamics model can simulate the sustainability performance of the city from the perspective of urban renewal, and can help decision makers to formulate appropriate strategies for sustainable urban development. In addition, it was found in the simulation results of the seven scenarios that increasing the ratio of in-site rehousing and off-site rehousing at the same time can promote sustainable urban development.